Answer:
according to me its just multiplying with the number ( -2)
like 9×(-2) = -18
36×(-2) = -72
Answer:
132::
Step-by-step explanation:
The power of g00gle <3
Uh I’m not even gonna question it but thanks for the free points ig? Lol
Answer:
Step-by-step explanation:
Join A and C and B and D. And add numbers to the angles formed on one of the diagonal
In triangles ABC and ADC,
Angle 1 = Angle 4
Angle 3 = Angle 2
AC = AC
Therefore, triangle ABC=ADC
Since, ABC=ADC
Similarly, triangle ABD= triangle CDB
Therefore, AB=CD and BC=DA